Ozone depletion, chlorine activation and water vapor observed in Spitsbergen - Wohltmann, Ingo (Universität Bremen, 2002)
This work discusses measurements of the ground based microwave Radiometer for Atmospheric Measurements (RAM), the retrieval of desired data products and their interpretation. The radiometer is operated at the Arctic NDSC station at Ny-Alesund, Spitsbergen. It measures water vapor at 22 GHz, ozone at 142 GHz and chlorine monoxide at 204 GHz. The first part of this work concentrates on the data retrieval. The second part deals with the determination of ozone loss rates, chlorine activation and denitrification. Measurements of chlorine monoxide, denitrification and reservoir gases are presented andexamined in the context of the current understanding of ozone chemistry.The third part examines the possibilities of retrieving tropospheric water vapor columns from the measurements of the radiometer.